Cost accounting : a managerial emphasis - Horngren, Charles T.; Datar, Srikant M.; Foster, George (Upper Saddle River, NJ : Pearson Prentice Hall, 2006)
Defined the cost accounting market and continues to innovate today by consistently integrating the most current practice and theory. This acclaimed, number one market-leading book embraces the basic theme of "different costs for different purposes." It reaches beyond cost accounting procedures to consider concepts, analyses, and management. This latest edition of "Cost Accounting "incorporates the latest research and most up-to-date thinking into all relevant chapters. Professional issues related to Management Accounting and Management Accountants are emphasized
Includes bibliographical references (p. 829-831) and indexes.
oif 13/03/15
Loan
Keywords: Cost accounting; Costs, Industrial; Managerial accounting